Effect of phosphate sorption on soil pH - Barrow, N. J.; Debnath, Abhijit; Sen, Arup (European journal of soil science, 2022)
The effect of reaction between soil and phosphate on pH has not previously been explored or explained. We incubated samples of a soil with calcium carbonate to give a range of pHCaCl2 from 4.2 to 7.2, and then measured the change in pH when these samples were reacted with phosphate solutions. These solutions were at the same pH as the soil to which they were added. We also measured exchangeable cations and cation exchange capacity. At low pH, reaction with phosphate increased pH; at high pH it decreased it. These effects are a consequence of the way that the charge on the phosphate molecules is distributed. Reaction with phosphate conveys negative charge to the soil. This charge may be located partly on the surface side of the adsorbed phosphorus molecule and partly on the solution side; that is either ‘inside’ or ‘outside’. At low pH the electric potential before reaction is less negative than at higher pH and it is easy to increase the negative charge inside the adsorbed phosphate molecules. Changes in charge inside the phosphorus atom have a large effect on potential; a small amount of charge is required to achieve the necessary electric potential. The charge conveyed to the surface is less than the mean charge of the ions in solution and the pH therefore increases. At high pH, because of the more‐negative potential, it is more difficult to increase the negative charge inside the adsorbed phosphorus atom. A larger fraction of the charge is therefore located outside it. A large amount of charge is required to achieve the necessary electric potential. This charge is greater than the mean charge on the ions in solution and the pH therefore decreases. The cation exchange capacity and the exchangeable cations reflect the charge inside the adsorbed phosphate molecule. At low to medium initial pH, reaction with phosphate did not decrease pH. The decreases in pH that are sometimes observed following application of phosphate are due to ancillary effects. Highlights The effect of reaction with phosphate on soil pH is not well understood. At low pH, reaction with phosphate increased soil pH; at high pH, it decreased it. These effects occur because the distribution of the charge on adsorbed phosphate changes with pH. These differences occur because of differences in the electrical potential.